The Value of Maslahah in the Application of Istihsan and Its Implementation in Cash Waqf Linked Sukuk - Anisatul Maghfiroh; Azwar Cholili; Imam Muslih; Muh. Syaukin Muttaqin; Sirajul Arifin (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
Modern economic and social developments brought Muslim societies into the context of increasingly complex transactions, including banking, etc. This challenge raises new problems that are not only solved by the sources of Qur'anic law and hadith. Istiḥsān is a method of establishing law that is postulated in Hanafi fiqh although its existence is still debated among fiqh scholars. This paper aims to examine the value of maslahah in the application of Istiḥsān. This research uses a desk-based research method, which includes searching relevant literature for data, compiling journal articles and books covering the subject matter of the research topic, and systematic analysis of the information obtained. The results of research in this paper show that istihsan uses maslahah mursalah as a method to get to maqashid shari'ah